OPERATIONAL MANAGEMENT OCEAN FISHING PORT OF BELAWAN NORTH SUMATERA PROVINCE - Yuliana '; Jonny Zain; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in 17-31 October 2016 in the ocean fishing port Belawan. This research aims toexamine operational management of Fishing Port Ocean the most important about elements and funcitionsapplication operational management. The study was conducted using a survey method. The data analysis is done by giving a description, explanation and discussion in accordance with the purpose of research. The study was conducted by taking the primary data and secondary data. Based on the research that the relationship port in private with PPS Belawan only as a partner of The Port in private of just issuing licenses provided in the ship's departure PPS Belawan to port form of license controlling interest, land rents and land ports janitorial services.Keyword : Operational management, Port in private, Belawan fishing port.